Conception of an endodontics questionnaire in undergraduate dental education - S Sacha; D Sonntag; S Rüttermann; S Gerhardt-Szép (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
The purpose of this study was to create a valid assessing instrument using a set of questions to examine preclinical dental education in endodontics. For this reason, we constructed the "German Endodontology Questionnaire" (GEndoQ), which assesses preclinical dental education in endodontics. In recent years and decades, various curricula in preclinical and clinical endodontic education have been evaluated at both national and international levels and the results published. However, the conception of the questionnaires that have been used have never been discussed or published.   The GEndoQ was constructed in five phases using the Delphi technique. In the first phase, the questionnaire was generated according to former questionnaires and publications through the first Delphi round and divided into 10 categories. In phases two and three, different expert panellists, such as specialists in endodontology and attendants of a master's degree programme in endodontology, used the Delphi technique to confirm the content validity of GEndoQ. The newest literature was implemented in phase four. In phase five, GEndoQ was finally completed after multiple abbreviations were included following feedback from the expert panellists who employed the think-aloud method.  Within the five phases, GEndoQ Version 5 was created comprising 49 questions in nine categories. This was done using different answer options. The Likert scale with six possible options to choose from was used the most: 1= don't agree at all; 2= don't agree; 3= undecided; 4= agree; 5= fully agree, 6= don't know. Seven questions could be answered in a free text format, while five questions were in a single-choice format, such as yes/no answers. The GEndoQ is a valid instrument for assessing preclinical dental education in endodontics. Future research will focus on further refining and validating the instrument, for example, within a pilot test. Additionally, the questionnaire should be translated into English and validated to make comparisons among international dental faculties easier.